Dire le fait divers - Stéphane Olivesi (Communication)
This article presents an analysis of the social functions of trivial news narratives in order to illustrate their mythological tendencies. The initial hypothesis consists of gathering trivial news items outside of the realm of the media. That is, from the angle of how they are discussed by individuals. The field work for this study was undertaken in Corsica. The study shows the form and power of the manifestation of the « real » within a culture which accords a specific place to the narration of news items. In restoring the strategic function of telling the truth to the statement, the analysis updates the role of narratives wherein the premise illustrates the cultural traits in which mythologies are rooted.